Pathological study of rabies in canine brain - Hemalatha, Lalrinkima; Nagarajan, S; Thangavelu, K; G, A., & Dhinakar Raj (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A pathological study on canine brain tissue suspected with rabies was carried out on necropsy cases received at the Department of  Veterinary Pathology, Madras Veterinary College Chennai, during April to September, 2019. Twenty-seven dogs presented for necropsy  were considered for the study. The clinical history, age, breed and sex wise distribution were recorded. Gross changes if any was  observed and samples of brain tissues were collected for histopathological studies. Brain impression smears were stained with William’s  modification of Van Gieson’s stain and observed for presence of Negri bodies. Out of 27 dogs examined eight cases showed presence  of Negri bodies. No significant gross changes were observable except for congestion, oedema and hemorrhages. Histopathological  studies revealed subdural hemorrhages, marked gliosis, perivascular lymphocytic cuffing, neutrophilic vacuolation and presence of  intracytoplasmic eosinophilic inclusions in neurons of cerebral grey matter.
Keywords: Canine; rabies; brain; gross; histopathology